Inverse association of serum carotenoid levels with prevalence of hypertension in the general adult population - Zhu, Xu; Shi, Mengshaw; Pang, Hui; Cheang, Iokfai; Zhu, Qingqing; Guo, Qixin; Gao, Rongrong; Liao, Shengen; Zhou, Yanli; Zhang, Haifeng; Li, Xinli; Yao, Wenming (Frontiers in Nutrition, 2022)
Carotenoid levels are inversely associated with blood pressure (BP). This study focused on the effects of individual and combined serum carotenoids on BP and hypertension, which have not been established to date. Data from National Health and Nutrition Examination Survey (NHANES) 2001–2006 were analyzed in this cross-sectional study. Multivariate logistic, linear, and weighted quantile sum (WQS) regression analyses were applied to explore the associations of six serum carotenoids (α-carotene, β-cryptoxanthin, lutein/zeaxanthin, trans-lycopene, trans-β-carotene, and cis-β-carotene), individually and in combination, with BP/hypertension. The linearity of correlations was further assessed using restricted cubic spline (RCS) regression. A total of 11,336 adults were included for analysis. Data from multivariate models showed that all six carotenoids were independently and negatively associated with both systolic blood pressure (SBP) and diastolic blood pressure (DBP; all p < 0.05). Compared to the first quartile, the fourth quartile of α-carotene (odds ratio [OR] = 0.64 [0.52–0.77]), β-cryptoxanthin (OR = 0.74 [0.60–0.90]), trans-β-carotene (OR = 0.50 [0.40–0.61]), and cis-β-carotene (OR = 0.47 [0.35–0.64]) were significantly and inversely related to hypertension (all p < 0.05). Moreover, WQS analysis revealed that the combination of all six serum carotenoids was negatively associated with BP and hypertension (all P<0.001), among which trans-β-carotene was the most significant contributor to the protective effect against hypertension (weight, 59.50%). Dose-response analyses demonstrated a linear inverse association of all carotenoids with hypertension (p for non-linearity > 0.05). Our collective findings indicate that higher levels of all six mixed serum carotenoids are correlated with decreased prevalence of hypertension, among which β-carotene exerts the most significant effect, which may provide a basis and direction for further studies.